For Feminist Killjoys between Love and Justice - Fatima Seedat (African Journal of Gender and Religion (AJGR))
First respondent for roundtable discussion from the Annual Desmond Tutu Centre for Religion and Social Justice Public Lecture on Economies of Violence.